Geological tour through the Orkney and the Shetland islands - Latocha, Agnieszka (Geotourism/Geoturystyka, 2025)
The main features of the landscape of the Orkney and the Shetland islands are presented in the article in the context of their geological and geomorphic development. The paper describes sites where rocks and landforms reflecting various stages of geological development appear at the surface. These include, among others, the oldest rocks on the European continent (remnants of the Caledonian orogen), rocks of an ancient ocean floor, granite intrusions, traces of former volcanic activity, landforms resulting from tectonics and glacial modelling. Also contemporary processes shaping the dynamic, rocky coastline are discussed, with attention paid to the influence of lithological and lithofacial variety of sediments on diversity of landforms within the cliffs and shore zone. The relationships between diversified geology, cultural and economic development of the islands and animate nature are mentioned, as well (eg., rocks used in the Neolithic buildings, oil and aggregate exploitation, nature resources and bird sanctuaries on the cliffs).